The Impact Of ‘Boko Haram’ On Trade In North-East Nigeria 2009-2015 - Ribadu, Abubakar Bashir (2018)
Terrorism has become a global phenomenon, which poses a threat to the development and continuous human existence. Nigeria’s North-East region (NE) has been ravaged by the “Boko Haram” (BH) terrorist activities over the past decade. This has persistently affected growth and development in the NE, particularly in terms of constant decline in taxes (government revenue) generated through trade and investments as well as import and export businesses. Therefore, due to the rise in the BH terrorist activities and the displacement of several thousands of inhabitants of the NE region, this study aims to firstly explore the nature of attacks and threats faced by investors in the NE by the BH terrorists. Secondly, this is also aimed at analyzing how the terrorist activities affect the local trade, as well as the import and export trade in the NE.